(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: In carrying out oversight functions, the Regional Representatives Council (DPRD) equipped with special rights that can support the effectiveness of the work as one of the institutions of control in the area. and most importantly that in determining whether or not accepted the draft budget proposed by the executive, the Regional Representatives Council (DPRD) had a very big right. Based on an evaluation of the State Audit Board (BPK) of the Republic of Indonesia through the representatives of North Sulawesi, assess the use of the Regional Budget (APBD) South Minahasa, from Fiscal Year 2009 to 2012 Budget gets a "disclaimer, meaning that can not be assessed and checks in Budget 2014, to use the Regional Budget (APBD) in 2013 there was an increase in ratings of disclaimer to the unnatural. This is due to Revenue and Expenditure Budget (APBD) South Minahasa District by each regional work units (SKPD) does not fit the designation and use of Revenue and Expenditure Budget (APBD) and assets much abused by the head of the regional work units (SKPD) and subordinates. This study aims: "To analyze the effect of supervisory functions Regional Representatives Council (DPRD) to use the Regional Budget (APBD) South Minahasa District". The method of analysis in this research is quantitative descriptive analysis method. Results of this research is that the supervision of Parliament is one of the determinant factors increase the effectiveness of the use of the budget, particularly in the South Minahasa District. In line with the Strategic Plan (Restra) South Minahasa District Government which sets one of the priority program is the use of the regional budget (APBD) is done effectively, efficiently and economically oriented public interest. Thus, efforts to increase the effectiveness of the use of local budgets is through an increase in the budget managers profesionalism apparatus itself by trying to implement i-budgeting. Keywords: Effect, Function Control, Parliament, Budget